Urgensi Indian Ocean Rim Association (IORA) dalam Diplomasi Maritim Indonesia - Ludiro Madu (Intermestic: Journal of International Studies, 2018)
This article examines the recent trend of increasing confidence in President Joko Widodo's administration to conduct multilateral diplomacy in order to complement bilateral diplomacy. Assuming that Indonesia as the chair of IORA 2015-2017 has strategic opportunities in designing, organizing and implementing IORA's pillars, goals, future direction. By using qualitative method, this article argues that some of the achievements of IORA in which Indonesian diplomacy has contributed during its leadership to face future challenges. Indonesia's maritime diplomacy during its leadership at IORA has significantly defined the fundamental contributions in directing the existence of IORA to anticipate future challenges.